Simvastatin promotes NPC1‐mediated free cholesterol efflux from lysosomes through CYP7A1/LXRα signalling pathway in oxLDL‐loaded macrophages. Issue 2 (15th September 2016) - Xu, Xiaoyang; Zhang, Aolin; Halquist, Matthew S.; Yuan, Xinxu; Henderson, Scott C.; Dewey, William L.; Li, Pin‐Lan; Li, Ningjun; Zhang, Fan
Abstract: Statins, 3‐hydroxyl‐3‐methylglutaryl coenzyme A reductase inhibitors, are the first‐line medications prescribed for the prevention and treatment of coronary artery diseases. The efficacy of statins has been attributed not only to their systemic cholesterol‐lowering actions but also to their pleiotropic effects that are unrelated to cholesterol reduction. These pleiotropic effects have been increasingly recognized as essential in statins therapy. This study was designed to investigate the pleiotropic actions of simvastatin, one of the most commonly prescribed statins, on macrophage cholesterol homeostasis with a focus on lysosomal free cholesterol egression. With simultaneous nile red and filipin staining, analysis of confocal/multi‐photon imaging demonstrated that simvastatin markedly attenuated unesterified (free) cholesterol buildup in macrophages loaded with oxidized low‐density lipoprotein but had little effect in reducing the sizes of cholesteryl ester‐containing lipid droplets; the reduction in free cholesterol was mainly attributed to decreases in lysosome‐compartmentalized cholesterol. Functionally, the egression of free cholesterol from lysosomes attenuated pro‐inflammatory cytokine secretion. It was determined that the reduction of lysosomal free cholesterol buildup by simvastatin was due to the up‐regulation of Niemann‐Pick C1 (NPC1), a lysosomal residing cholesterol transporter. Moreover, the enhanced enzymatic production of 7‐hydroxycholesterol by cytochrome P450 7A1 and the subsequent activation of liver X receptor α underscored the up‐regulation of NPC1. These findings reveal a novel pleiotropic effect of simvastatin in affecting lysosomal cholesterol efflux in macrophages and the associated significance in the treatment of atherosclerosis.